The Ab Initio Calculations on the Areal Specific Resistance of Li‐Metal/Li7La3Zr2O12 Interphase. Issue 6 (24th April 2019) - Gao, Jian; Guo, Xuyun; Li, Yutao; Ma, Zhaohui; Guo, Xiangxin; Li, Hong; Zhu, Ye; Zhou, Weidong
Abstract: The solid–solid interfacial impedance between the garnet electrolyte and Li metal anode is one of the major challenges for garnet's application in all‐solid‐state batteries. The areal specific resistance (ASR) is investigated by ab initio calculations in this article, to predict the intrinsic ASR as lower limitation. The Li ion migration across the interphase is divided into two steps: 1) Li "intercalation" from Li‐metal to the LLZO, forming a Li‐rich interphase beneath the surface of LLZO, and 2) Li migration in the Li‐rich interphase within LLZO. The first step is investigated by climbing image nudged elastic band (CI‐NEB), resulting in barrier energy lower than 0.37 eV compared to experimental 0.34 eV of the garnet bulk phase. The second step is investigated by ab initio molecular dynamic simulations (AIMD), indicating that the Li‐rich interphase's conductivity is lower by about 1–2 orders of magnitude compared to the bulk phase. As a result, the sum theoretical intrinsic ASR is as low as 0.01 Ω cm 2, suggesting high ASR in practicable battery arises from surficial impurity Li2 CO3 rather than intrinsic ionic resistance. However, difficulties of removing Li2 CO3 lie in that Li7 La3 Zr2 O12 can thermodynamically decompose into reactive Li2 O to form high resistant Li2 CO3 . Abstract : Understanding the origin of high interfacial resistance between Li/Li7 La3 Zr2 O12 (LLZO) is crucial for the power density and stability. Here, ab initio calculations confirm the moderate intrinsic areal specific resistance and thermodynamic decomposition tendency of LLZO into Li2 O. The atmosphere CO2 sets up Li2 CO3 barriers to prohibit Li permeation, and H2 O increases the amount of Li2 CO3 by exchanging more Li with H.